Implementasi Kewarganegaraan Digital sebagai Sumber Belajar oleh Guru PPKn : Strategi dan Kendala di SMAN 2 Sukabumi (Lembaga Pengembangan Kinerja Dosen, 2025)
The advancement of information technology has significantly influenced learning practices in the digital era. In the field of education, digital citizenship has become a crucial component for enhancing the quality of learning, particularly in the subject of Pancasila and Civic Education (PPKn). This study aims to analyze the strategies employed by PPKn teachers in implementing digital citizenship as a learning resource at SMAN 2 Sukabumi and to identify the challenges encountered. The research uses a qualitative method with a case study approach, employing data collection techniques such as observation, in-depth interviews, and document analysis. The findings reveal that the implementation strategies include: (1) digital ethics education, (2) utilization of online learning resources, (3) classroom discussions on current issues, (4) collaborative creative projects, and (5) digital safety training. The main challenges identified are limited technological infrastructure, the digital literacy gap between teachers and students, a lack of relevant content, and difficulties in assessing learning effectiveness. This study recommends enhanced collaboration between schools, government, and related stakeholders to strengthen infrastructure and provide ongoing digital literacy training.